Noise statistics in a fast digital radio receiver: The Bedlam backend for the Parkes radio telescope - Bray, J.; Ekers, Ronald; Roberts, P. (2013)
The digital record of the voltage in a radio telescope receiver, after frequency conversion and sampling at a finite rate, is not a perfect representation of the original analog signal. To detect and characterise a transient event with a duration comparable to the inverse bandwidth it is necessary to compensate for these effects, altering the statistical properties of the signal and making it difficult to determine the significance of a potential detection. We present an analysis of these modified statistics and demonstrate them with experimental results from Bedlam, a new digital backend for the Parkes radio telescope. © 2013 Springer Science+Business Media Dordrecht.